Management analysis of dairy cow herd enterprises in the Kansas Farm Management Association - F.D. DeLano; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 1994)
Actual records of dairy cow herd enterprises from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns over variable costs from 17,900 to 27,000 per farm for a 100-cow dairy herd in favor of herds with higher milkproducing cows. Cost per hundred weight of milk produced per cow decreased for the higher-producing herds compared with lowerproducing herds, even though total cost per cow increased. In 1993, for every extra 1.00 spent on feed and other variable costs, the higher producing herds earned 2.34. This was a 234% return per dollar invested.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Economics; Dairy; Management